Effect of Lorazepam on the Development of the Hairy Maggot Blow Fly, Chrysomya rufifacies (Macquart): Implication for Forensic Entomology - Sarika Annasaheb Bansode; Vitthal Ramrao More (Journal of Toxicology)
Entomotoxicology is based on using insect evidence recovered from a dead body to find out the cause and time of the death. Drugs can accumulate in fly larvae when they ingest the flesh of deceased persons and alter the normal development of the fly causing implications in calculating postmortem intervals. Lorazepam is an antidepressant generally used to treat anxiety. Larvae of Chrysomya rufifacies were fed on the beef liver mixed with lorazepam to study the effect of lorazepam on the developmental rate of larvae and to count delay in postmortem interval. Larvae grown on the beef liver with different doses of lorazepam showed delayed development as compared to normal larvae. The life cycle durations in experimental cultures with different concentrations of lorazepam completed in 1 ppm (272.56 hrs), 2 ppm (289.23 hrs), 3 ppm (324.10 hrs), and 4 ppm (350.72 hrs), while in the control culture life cycle completed in 257.26 hrs. The length, weight, and width of the larvae treated with lorazepam were smaller than the untreated culture. Length, weight, and width decreased with increased concentration of lorazepam. This delay in development ultimately affects the postmortem interval. That is why prior knowledge of the life cycle of flies with respect to various drugs needs to be studied, and these baseline data can be used to calculate postmortem interval and cause of death.